Determinan Penerapan Perilaku Hidup Bersih dan Sehat (PHBS) di Masyarakat Pedesaan Kabupaten Batu Bara - Nadiva Olyza Rangkuti; Asriwati Asriwati; Ramadhani Syafitri Nasution (Jurnal Kesehatan Amanah, 2026)
The implementation of Clean and Healthy Living Behavior (PHBS) in Hamlet II, Kuala Tanjung Village, is still relatively low, where 62% of the community has not implemented PHBS properly, which has the potential to increase the risk of infectious diseases. This study aims to analyze the factors that affect the implementation of PHBS in the region. This type of research is quantitative with a cross sectional study design that will be carried out from October 2024 to August 2025. The research sample amounted to 84 respondents which were determined through random sampling techniques. Data analysis used logistic regression. Multivariate analysis showed that the variable of infrastructure facilities was the most dominant factor influencing the implementation of PHBS in Kuala Tanjung Dusun II Village. In conclusion, the implementation of PHBS is influenced by factors of knowledge, attitudes, infrastructure, and social support of the community. It is recommended that the village government and health workers improve the availability and quality of infrastructure facilities such as handwashing stations and healthy latrines, especially in areas that still lack basic facilities, in order to support clean and healthy living behaviors in a sustainable manner.